PROMOTING DISCOVERY LEARNING METHOD FOR EFL STUDENTS IN READING COMPREHENSION - Muliati Muliati; Ulfah Syam (Universitas Muhammadiyah Makassar, 2020)
This research aims to examine the impact of discovey learning method and to know the significance of discovey learning method on students’ reading comprehension. This research used pre-experimental method with one group in pre test and post test. The treatment conducted after the pre test and before post test. The impact of discovery learning method and the significance of discovery learning method would be considered in learning reading. This research is restricted to students’ reading comprehension in SMPN 01 Barru. The finding revealed that before applying discovery learning method students have difficulties in answering reading comprehension test. Meanwhile, after giving treatment and disrtributing post-test, the students have reading skill increase significantly. However, the students resource issues that are dominated by the difficulties in reading English, the limitation of vocabulary that they have, and the strategies that teacher used in teaching and learning reading. The Significance of the research are expected to provide data and information about the implementing of discovey learning method teaching and learning reading. By knowing the students’ comprehension in reading English, the teacher can apply designing material, strategies, and activities based on their students’ reading comprehension. It is obviously more effectively run the teaching and learning reading in the classroom.